An overview of solvent management and emissions of amine-based CO2 capture technology - Mazari, S.A.; Si Ali, B.; Jan, B.M.; Saeed, I.M.; Nizamuddin, S. (Elsevier, 2015)
Increasing global carbon dioxide (CO2) emissions are a rising concern for the global climate change. Amine-based post-combustion CO2 capture (PCC) technology is one of the mature options to contribute to the mitigation of these emissions. The technology is approaching toward its commercialization. However, there are two important problems, which should properly be addressed, solvent management and the amine-based PCC emissions. Major losses in amines are due to the oxidative and thermal degradation. Concentration of oxygen (O-2) is the driving force for the oxidation. Temperature, CO2 loading and amine concentration affect both thermal and oxidative degradation. This manuscript reviews solvent selection, thermal and oxidative degradation of amines used for CO2 capture. Furthermore, amine-based PCC emissions have also been highlighted, with some of their concerns. Based on literature reviewed and discussions provided, conclusions are made. In addition, some of the future work is also directed in form of suggestions. (C) 2015 Elsevier Ltd. All rights reserved.